Bright white light up-conversion luminescence from Yb3+/Er3+/Tm3+ tridoped gadolinium gallium garnet nano-crystals for multicolor and white light-emitting diodes - (:unkn) unknown (My University, 2022)
Gadolinium Gallium Garnet nanophosphors with Yb3+/Er3+/Tm3+ triply-doped ions were synthesized via the Solgel Pechini method and annealed at different temperatures ranging from 800 to 1200 degrees C. The approximate average crystallite sizes were determined within the range of 26-56 nm by using X-ray diffraction analysis. Color-tunable up-conversion emission was explored in nanomaterials by varying excitation power under 975 nm excitation wavelength by varying excitation power and Tm3+ concentration for white light emission. Bright white light up-conversion luminescence from Yb3+/Er3+/Tm3+ tridoped Gd3Ga5O12 was recorded. The color quality coordinates for Gd3Ga5O12:2%Yb3+/1%Er3+/1.5%Tm3+ nanophosphors annealed at 1000 degrees C were found to be x = 0.3244, y = 0.3297 at room temperature under 975 nm infrared excitation, which falls within the white zone of the 1931 International Commission on Illumination diagram. Nanophosphors show extreme near-infrared radiation at 800 nm, which is also beneficial to deeper tissue penetration and promotes plants\" growth.
Keywords: Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Optik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Optics; Natural Sciences; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); OPTİK; Temel Bilimler (SCI); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); OPTICS; PHYSICS; Natural Sciences (SCI); Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Fizik Bilimleri; Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences; Nanophosphors; Gadolinium gallium garnet (GGG); Up-conversion; Color chromaticity coordinates; WLED; NANOCRYSTALLINE GD3GA5O12; ENERGY-TRANSFER; EMISSION; SPECTROSCOPY; GREEN; /ER3+; BLUE; LN